Synergistic effects of maize-pigeon pea intercropping and low-dose fertilization on fall armyworm control - Zanzana, K.; Sinzogan, A.; Tepa-Yotto, G.; Dannon, E.A.; Toffa, J.; Modibo, K.A.; Goergen, G.; Tamo, M. (2025)
The fall armyworm (FAW), Spodoptera frugiperda;(JE Smith; Lepidoptera, Noctuidae), is a major threat to maize crop. Although several studies showed that intercropping maize with legumes and good fertilizing of maize can reduce the pest attacks on the maize crop, the synergistic effect of these two approaches is under-studied. The aim of this study is to assess the synergy between maize-pigeon pea intercropping and low fertilization on FAW larval infestation, maize plant growth, natural enemy presence, and grain yield. A field experiment was conducted at IITA, Benin station using a complete randomized block design with three replicates. Fertilization treatments included three low doses: 150 kg ha− 1 NPKS BZn (13-17-17-6-0.5-1.5%), 150 kg ha− 1 NPKS BZn+ 25 kg ha− 1 urea (46% N), 150 kg ha− 1 NPKS BZn+ 50 kg ha− 1 urea (46% N), along with a no-fertilization control. Results showed that applying low NPKS BZn fertilization at 150 kg ha− 1 to maize intercropped with Pigeon pea significantly reduced FAW larval density, leaf damage severity, induced the highest height and grain yields and increased populations of parasitoids. These findings support integrated soil fertility management and demonstrate that companion plant with Pigeon pea can be an effective cultural control strategy for FAW. This method provides a sustainable alternative to synthetic insecticides, promoting environmentally friendly agricultural practices.